A study on direct antimicrobial susceptibility testing of positive blood culture broth using BacT/Alert 3D microbial identification system in a tertiary care hospital - Kesavan R; Ramani CP; Sudha N; Rajasree S (Asian Journal of Medical Sciences, 2024)
Background: Sepsis is one of the major causes of mortality and morbidity in hospitals. Bloodstream infections (BSI) affect approximately 2% of all hospitalized patients and 70% of patients admitted to the Intensive Care Units. Detection of BSI is one of the most important tasks performed in the microbiology laboratory. Aims and Objectives: This study aims to evaluate direct antimicrobial susceptibility tests (DAST) from positive blood culture broth in suspected bacteremia and compare the DAST and conventional antimicrobial susceptibility testing (CAST) of the isolates. Materials and Methods: A descriptive study involving a total of 112 aerobic blood culture bottles flagged positively by the automated Identification System (Bac T/Alert3D) was processed. The bacteria were pelleted by two-step centrifugation of the broth from the bottle and used to make a smear for Gram stain as well as an inoculum for antimicrobial sensitivity testing by Kirby–Bauer disk diffusion method. Results: Out of 842 blood culture samples, 112 flagged positive cultures were subjected to direct gram film, 28 were found to be polymicrobial, 24 Gram-positive cocci, and 60 were Gram-negative bacilli. There was a complete match between the direct Gram stain result from the positive bottle and the Gram stain from subcultures from the bottles obtained after overnight culture on solid media. Conclusion: This study has demonstrated good concordance between the DAST and CAST results. Hence, direct AST can be implemented in a routine diagnostic laboratory. Direct AST will be helpful to decrease the turnaround time and to start early antimicrobial therapy in critically ill patients.